The potential DNA methylation markers of cardiovascular disease in patients with type 2 diabetes - Yunbiao He; Xia Chen; Mingliang Liu; Lei Zuo; Zhiyu Zhai; Long Zhou; Guangzhen Li; Li Chen; Guolong Qi; Chunxia Jing; Guang Hao (BMC, 2023)
Abstract Background DNA methylation is associated with cardiovascular (CV) disease. However, in type 2 diabetes (T2D) patients, the role of gene methylation in the development of CV disease is under-studied. We aimed to identify the CV disease-related DNA methylation loci in patients with T2D and to explore the potential pathways underlying the development of CV disease using a two-stage design. Methods The participants were from the Jinan Diabetes Cohort Study (JNDCS), an ongoing longitudinal study designed to evaluate the development of CV risk in patients with T2D. In the discovery cohort, 10 diabetic patients with CV events at baseline were randomly selected as the case group, and another 10 diabetic patients without CV events were matched for sex, age, smoking status, and body mass index as the control group. In 1438 T2D patients without CV disease at baseline, 210 patients with CV events were identified after a mean 6.5-year follow-up. Of whom, 100 patients who experienced CV events during the follow-up were randomly selected as cases, and 100 patients who did not have CV events were randomly selected as the control group in the validation cohort. Reduced representation bisulfite sequencing and Targeted Bisulfite Sequencing were used to measure the methylation profiles in the discovery and validation cohort, respectively. Results In the discover cohort, 127 DMRs related to CV disease were identified in T2D patients. Further, we validated 23 DMRs mapped to 25 genes, of them, 4 genes (ARSG, PNPLA6, NEFL, and CRYGEP) for the first time were reported. There was evidence that the addition of DNA methylation data improved the prediction performance of CV disease in T2D patients. Pathway analysis identified some significant signaling pathways involved in CV comorbidities, T2D, and inflammation. Conclusions In this study, we identified 23 DMRs mapped to 25 genes associated with CV disease in T2D patients, of them, 4 DMRs for the first time were reported. DNA methylation testing may help identify a high CV-risk population in T2D patients.